Highly expressed SERCA2 triggers tumor cell autophagy and is a druggable vulnerability in triple-negative breast cancer - Minmin Fan; Jian Gao; Lin Zhou; Wenwen Xue; Yixuan Wang; Jingwei Chen; Wuhao Li; Ying Yu; Bo Liu; Yan Shen; Qiang Xu (Elsevier, 2022)
Chemoresistance remains a major obstacle to successful treatment of triple negative breast cancer (TNBC). Identification of druggable vulnerabilities is an important aim for TNBC therapy. Here, we report that SERCA2 expression correlates with TNBC progression in human patients, which promotes TNBC cell proliferation, migration and chemoresistance. Mechanistically, SERCA2 interacts with LC3B via LIR motif, facilitating WIPI2-independent autophagosome formation to induce autophagy. Autophagy-mediated SERCA2 degradation induces SERCA2 transactivation through a Ca2+/CaMKK/CREB-1 feedback. Moreover, we found that SERCA2-targeting small molecule RL71 enhances SERCA2-LC3B interaction and induces excessive autophagic cell death. The increase in SERCA2 expression predisposes TNBC cells to RL71-induced autophagic cell death in vitro and in vivo. This study elucidates a mechanism by which TNBC cells maintain their high autophagy activity to induce chemoresistance, and suggests increased SERCA2 expression as a druggable vulnerability for TNBC.